IMPLEMENTASI PEMROGRAMAN BERORIENTASI OBJEK, OBSERVER DESIGN PATTERN, DAN SCRIPTABLEOBJECT DALAM PEMBUATAN SOFTWARE ARCHITECTURE GAME 3D ACTION RPG "NEVERGREEN" - Rainaldi Satria Sukarno (2023)
As the scope of a game project expands, its development becomes increasingly complex. Developing a game with bad software architecture can lead to various issues, such as high bug risks, project delays, and higher costs. Therefore, a solution is needed to overcome these challenges. While there have been various efforts to address issues related to software architecture, there is no in-depth research on this topic in the context of creating 3D action RPG games, particularly those focused on using object-oriented programming, observer design patterns, and ScriptableObject. Hence, this research aims to create reliable software architecture by applying these three programming principles. As a case study, a game prototype named NeverGreen was created. NeverGreen is a 3D action RPG game that addresses the issue of bioterrorism, developed using Unity 2022. This research adopts the Game Development Life Cycle (GDLC) method by Heather Chandler. The research's results indicate that the integration of these three programming principles successfully produces the case study game, meeting the required specifications without compromising quality. The software architecture is modular, flexible, extensible, reusable, editable, and debuggable.